Problems of Implementing Village Origin Rights in Indonesia: Lessons Learned from Nagari in West Sumatra and Desa Pakraman in Bali - Asrinaldi, Asrinaldi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
Local democracy in the village is essentially based on these rights of origin and traditional rights. This paper aims to discuss the problems of villages in exercising their rights of origin in Indonesia. To understand how these rights of origin are implemented, this article refers to the practice of Nagari as a customary legal community unit in West Sumatra Province. Not only that, enrichment related to implementing rights of origin also refers to Desa Pakraman in Bali Province. This article uses a literature study derived from documents that have been published from various sources such as articles in scientific journal, mass media news, and official government documents. This article finds that problems in the application of origin and traditional village rights arise because of strict government regulations that encourage village governments to focus on carrying out governance functions in their area. Using the principles of recognition and subsidiarity in the administration of village government results in an attitude of ambiguity in the administration of village government. As a result, the village government prefers to implement the household authority handed over to it accompanied by a budget through Village Fund transfers rather than developing the original rights that have become the identity of pre-existing local democracy.